REKONSTRUKSI â€œISLAM TEH SUNDA, SUNDA TEH ISLAMâ€ - MBP, Abdurrahman (Asy-Syari’ah, 2015)
This paper describes the background of the â€œIslam teh Sunda dan Sunda teh Islamâ€ means that â€œIslam is the same as the Sunda and Sunda that is Islamâ€, the term, was introduced by Haji Endang Saefudin Ansari. To know the term, the authors will focus on the discussion of the history of the emergence of the term â€œIslam teh Sunda dan Sunda teh Islamâ€, the development of the term â€œIslam teh Sunda dan Sunda teh Islamâ€, and the reconstruction of the term â€œIslam teh Sunda dan Sunda teh Islamâ€. The findings were obtained by the author of the term â€œIslam teh Sunda dan Sunda teh Islamâ€, namely: (1) the term â€œIslam teh Sunda dan Sunda teh Islamâ€ is the reality of the Sundanese people who have accepted Islam because in harmony with the values of their kesundaan; (2) alignment of the Sunda and Islam looks of their belief in the existence of God the Creator and Owner of Nature (monotheism) as well as the behavior and ethics of Sunda in harmony with the manners and morals of Islam; and (3) Reconstruction of the term â€œIslam teh Sunda dan Sunda teh Islamâ€ carried out by the foundation reaffirm tawhidullÃ¢h (belief in one Allah), build supporting pillars in the form of refund Hanif nature of mankind and formulate the roof as an umbrella that is fiqhiyyah rules especially rule â€œal-â€˜Ã¢dah al-muhakkamahâ€.